2023
DOI: 10.1111/ejn.16184
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in pregnancy—Long‐term effects on offspring hypothalamic‐pituitary‐adrenal axis and associations with placental cortisol metabolism: A systematic review

Tabia Volqvartz,
Helena Hørdum Breum Andersen,
Lars Henning Pedersen
et al.

Abstract: Obesity, affecting one in three pregnant women worldwide, is not only a major obstetric risk factor. The resulting low‐grade inflammation may have a long‐term impact on the offspring's HPA axis through dysregulation of maternal, placental and fetal corticosteroid metabolism, and children born of obese mothers have increased risk of diabetes and cardiovascular disease. The long‐term effects of maternal obesity on offspring neurodevelopment are, however, undetermined and could depend on the specific effects on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 195 publications
0
4
0
Order By: Relevance
“…After birth, the HPA axis is able to regulate responses to adverse conditions, acting on the metabolism of carbohydrates, proteins and lipids, and participating in anti-inflammatory effects and suppression of the immune response [138,139]. A study found that maternal diabetes with high cortisol levels is linked to changes in the development of the brain's cortical, neuroendocrine system by reducing the number of hippocampal neurons [140]. This is accompanied by disruptions in the foetal HPA axis, resulting in structural changes such as cortical thinning, enlarged amygdala, and impaired development of the foetal cerebellum [141,142].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After birth, the HPA axis is able to regulate responses to adverse conditions, acting on the metabolism of carbohydrates, proteins and lipids, and participating in anti-inflammatory effects and suppression of the immune response [138,139]. A study found that maternal diabetes with high cortisol levels is linked to changes in the development of the brain's cortical, neuroendocrine system by reducing the number of hippocampal neurons [140]. This is accompanied by disruptions in the foetal HPA axis, resulting in structural changes such as cortical thinning, enlarged amygdala, and impaired development of the foetal cerebellum [141,142].…”
Section: Discussionmentioning
confidence: 99%
“…This is accompanied by disruptions in the foetal HPA axis, resulting in structural changes such as cortical thinning, enlarged amygdala, and impaired development of the foetal cerebellum [141,142]. The modifications in brain structures caused by cortisol have been consistently linked to impairments in both cognitive and emotional development, as well as basal high cortisol levels in children [140][141][142]. However, the exact molecular and cellular mechanism by which diabetes during pregnancy affects the development of the brain is still unknown [143].…”
Section: Discussionmentioning
confidence: 99%
“…It metabolises active glucocorticoids (cortisol in humans and corticosterone in rats) into inactive glucocorticoids, thereby shielding the fetus against excessive glucocorticoid exposure from the mother [106][107][108]. Although the placenta metabolises a significant proportion of cortisol (80-90% during gestation), excess cortisol may reach the fetus and the ʹbarrierʹ can be further weakened by maternal high maternal glucocorticoid or placental dysfunction, which is commonly caused by increased oxidative stress resulting in hypoxia, allowing increased transfer of glucocorticoids from mother to fetus [19,65,109]. The HPA axis dysregulation with elevated basal glucocorticoid has been investigated in type 2 diabetes mellitus (T2DM) similarly to maternal stress and adverse fetal outcomes in pregnancy [9][10][11].…”
Section: Role Of Maternal Hypothalamic-pituitary-adrenal (Hpa) Axis I...mentioning
confidence: 99%
“…It metabolizes active glucocorticoids (cortisol in humans, and corticosterone in rats) into inactive glucocorticoids, thereby shielding the fetus against excessive glucocorticoid exposure from the mother, as shown in ( Figure 1 ) [ 85 , 86 ]. Although the placenta metabolizes a significant proportion of cortisol (80–90% during gestation), excess cortisol may reach the fetus, and the ‘barrier’ can be further weakened by maternal high maternal glucocorticoid or placental dysfunction, which is commonly caused by increased oxidative stress, resulting in hypoxia, allowing for the increased transfer of glucocorticoids from the mother to the fetus [ 16 , 54 , 87 ]. The following section describes T2DM, prevalences, pregestational consequences associated with fetal programming, and associated diseases in adulthood.…”
Section: Role Of the Maternal Hypothalamic–pituitary–adrenal (Hpa) Ax...mentioning
confidence: 99%